Chronic exposure to paroxetine or bupropion modulates the pubertal maturation and the reproductive system in female rats - Ulker, Nazife; Yardimci, Ahmet; Tektemur, Nalan Kaya; Colakoglu, Neriman; Ozcan, Mete; Canpolat, Sinan; Kelestimur, Haluk (Elsevier, 2020)
Antidepressant drugs are globally used to treat several psychiatric disorders in pediatric patients and their prescription has continued to increase in recent years, especially among girls. In addition to its well-known metabolic and gastrointestinal side effects, antidepressants can cause sexual dysfunction in adults. However, the effects of the antidepressants on puberty onset and reproductive system remain unclear in children and adolescents. Therefore, the goal of this study is to examine the effects of chronic postnatal antidepressant drugs, paroxetine or bupropion, treatments on puberty onset and reproductive system components in female rats weaned at postnatal day (PND) 21. Female rats (n = 10 for each group) were exposed to vehicle (0.2 mL of saline), paroxetine (3.6 mg/kg in 0.2 mL of saline) or bupropion (17 mg/kg in 0.2 mL of saline) daily by oral gavage from the PND 21 to PND 90- 93. Chronic paroxetine or bupropion treatments advanced the puberty onset, but the difference was statistically significant in only the paroxetine group. The exposure to bupropion significantly decreased the serum anti-Milllerian hormone (AMH) levels and luteinizing hormone (LH) levels. There were increases in serum estradiol levels by both antidepressant treatments and the significance was found in only the paroxetine group. Consistent with these results, histopathologic changes were observed in the ovary and uterus tissues taken from both antidepressant-treated rats. The obtained results of chronic postnatal exposure to paroxetine or bupropion may change the timing of puberty onset and lead to disruption of reproductive functions in females.
Keywords: Paroxetine; Bupropion; Puberty onset; Reproductive functions; Female rat